Transnational forest fire fighting: the Malaysian experience - Mat Said, Aini; Ahmadun, Fakhru'l-Razi; Daud, Mohamed; Wahid, Mohammad Hamdan (MCB University Press, 2000)
The forest fire experiences of Malaysia, Singapore, the Philippines and Thailand in 1997 are reviewed. The problems of transnational co‐operation in such cases are examined and the resulting joint lessons are presented.